Choosing Across Cultures: The Effect of Choice Complexity on Treatment Outcomes. (20th March 2015) - Brown, Jill A.; Oikawa, Masanori; Rose, Jason P.; Haught, Heather M.; Oikawa, Haruka; Geers, Andrew L.
Abstract: Prior research has revealed that having choice over treatments can improve their efficacy. However, it is currently unknown if the benefits of treatment choice hold for complex decisions and different cultures. The effects of differing numbers of treatment options were explored across two cultural contexts: United States and Japan. Participants were exposed to an uncomfortable stimulus and provided with up to 15 placebo treatment options they believed would reduce discomfort. There was a significant interaction such that participants from Japan benefited most from fewer treatment options (2 and 5) compared with more treatment options (10 and 15). Participants from the United States, however, showed either no change in discomfort or less discomfort as the number of choices increased. Additionally, participants from Japan reported less satisfaction with the decision process when they had more treatment options to choose from whereas U.S. participants reported similar, if not slightly higher, satisfaction with more treatment options. Further, a second study indicated that a positive experience with the decision process mediated the relationship between choice complexity and treatment efficacy for Japanese participants. These data demonstrate the importance of culture and choice complexity when discussing treatment choice and resulting outcomes in the medical context. Copyright © 2015 John Wiley & Sons, Ltd.